2013
DOI: 10.1088/0004-637x/773/2/153
|View full text |Cite
|
Sign up to set email alerts
|

PHYSICAL PROPERTIES OF SPECTROSCOPICALLY CONFIRMED GALAXIES ATz⩾ 6. II. MORPHOLOGY OF THE REST-FRAME UV CONTINUUM AND Lyα EMISSION

Abstract: We present a detailed structural and morphological study of a large sample of spectroscopicallyconfirmed galaxies at z ≥ 6, using deep HST near-IR broad-band images and Subaru optical narrowband images. The galaxy sample consists of 51 Lyα emitters (LAEs) at z ≃ 5.7, 6.5, and 7.0, and 16 Lyman-break galaxies (LBGs) at 5.9 ≤ z ≤ 6.5. These galaxies exhibit a wide range of restframe UV continuum morphology in the HST images, from compact features to multiple component systems. The fraction of merging/interacting… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
113
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 99 publications
(136 citation statements)
references
References 98 publications
23
113
0
Order By: Relevance
“…8) HDF 850.1 is the only known SMG in the galaxy overdensity at z = 5.2 ), suggesting a rare, transient event within this galaxy group, namely a very large starburst, characteristic of gas-rich mergers. 9) The linear sizes of the two objects in HDF 850.1 (Table 2) are about the same as the 1 to 2 kpc sizes that are measured for individual galaxies themselves at z = 5 (e.g., Oesch et al 2010;Jiang et al 2013). This also suggests that rather than parts of a large disk, they are pieces in the merger assembly of what will be a single, larger galaxy at later times.…”
Section: Conclusion: Hdf 8501 Is Similar To Other High-z Ulirg and Ssupporting
confidence: 63%
“…8) HDF 850.1 is the only known SMG in the galaxy overdensity at z = 5.2 ), suggesting a rare, transient event within this galaxy group, namely a very large starburst, characteristic of gas-rich mergers. 9) The linear sizes of the two objects in HDF 850.1 (Table 2) are about the same as the 1 to 2 kpc sizes that are measured for individual galaxies themselves at z = 5 (e.g., Oesch et al 2010;Jiang et al 2013). This also suggests that rather than parts of a large disk, they are pieces in the merger assembly of what will be a single, larger galaxy at later times.…”
Section: Conclusion: Hdf 8501 Is Similar To Other High-z Ulirg and Ssupporting
confidence: 63%
“…At z > 4, there are several α measurements reported by Curtis-Lake et al (2014); Huang et al (2013); Jiang et al (2013); Grazian et al (2012). However, these data points of α are largely scattered (the right panel of Figure 10).…”
Section: Size-luminosity Relationmentioning
confidence: 82%
“…Larger, more sensitive surveys at FIR wavelengths with ALMA would better address this question. At rest-UV wavelengths, Jiang et al (2013) found that ∼ 50% of bright z ∼ 6 galaxies show evidence for recent mergers or interactions in HST observations. However, observing such faint features in luminous quasar host galaxies would be exceedingly difficult.…”
Section: Discussionmentioning
confidence: 99%